Designing and implementing healthcare technology for rehabilitation processes—a wicked problem? Lessons learned from a collaboration between healthcare personnel and technologists - Jo Inge Gåsvær; Ilona Heldal; Tobba Sudmann (Digital Health)
Introduction This paper presents the results of a critical ethnography study on the design and implementation of Ad Voca, a web platform for rehabilitation purposes that can be integrated with the electronic health record. The process involved technologists and healthcare personnel collaborating to harness the platform's design, amendments, and implementation strategies. Methods The design and implementation of a web platform for rehabilitation is an eminent case for an explorative action learning study. The empirical material is compiled through participant observation, analysis of written sources, and interviews. The theory of wicked problems is used as an analytical lens. Findings New challenges emerged throughout the project period. Negotiations related to trade-offs between clinical and IT capabilities, decision-making on project goals, resource allocations, priority setting between re-design or new design, and compatibility with other IT solutions for healthcare. Participants were creative, flexible, conservators of professional standards, and appreciated mono- and cross-professional work divisions. When stakeholders were brought together across technology and healthcare settings, suggestions about what was needed to be fit-for-purpose-design and to secure user satisfaction were abundant. Leaders play a key role in these processes. Conclusion and recommendations Good intentions and collaborative efforts must be supported by systems thinking, management involvement, and critical appreciation of the conditions for collaboration, commercial value, and clinical value. Systems thinking and adaptive strategies relieve front-line workers (healthcare and IT teams) from the responsibility of commercial and end-user success, facilitate creativity, and contribute to new solutions and perseverance in design processes.